A new species of the genus Garra Hamilton (Teleostei: Cyprinidae) from Northeast India - Roni, Narengbam; Chinglemba, Yengkhom; Rameshori, Yumnam; Vishwanath, Waikhom (Zootaxa, 2019)
A new species of Garra with a rostral proboscis is described from the Barak River drainage in Manipur, India. Garra paratrilobata, new species, is distinguished from its congeners in having the combination of the following characters: a prominent trilobed proboscis, the median lobe with 5–7 uni- to tricuspid tubercles on its anterior margin and 4–6 minute tubercles on its anteroventral margin; lateral lobe of the proboscis with 3–4 minute tubercles; lateral surface of the snout lobular, with 6–9 tubercles; 33–34 lateral-line scales; and the rostral surface concave, creased and depressed.